2018
DOI: 10.3329/bjar.v43i1.36154
|View full text |Cite
|
Sign up to set email alerts
|

Influence of paclobutrazol on growth, yield and quality of mango

Abstract: A study on the effect of paclobutrazol on vegetative growth, harvest time, yield and quality of mango cv. BARI Mango-3 (Amrapali) was conducted at the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…The highest carbohydrate content was found to be 2.62267 mg/g. This finding is partially agrees with previous reports on mango [35]. It is well known that paclobutrazol interferes with the hormone abscisic acid's production [36].…”
Section: Resultssupporting
confidence: 93%
“…The highest carbohydrate content was found to be 2.62267 mg/g. This finding is partially agrees with previous reports on mango [35]. It is well known that paclobutrazol interferes with the hormone abscisic acid's production [36].…”
Section: Resultssupporting
confidence: 93%
“…This reduction in gas exchange during the flowering phase may be related to decreases in air temperature (Figure 1). A greater photosynthetic efficiency promotes a greater accumulation of carbohydrates, which can contribute significantly to flowering, fruiting and fruit production [23]. Singh et al (2017) [24], studying the effects of PBZ on the physiological characteristics of lychee, also reported higher A, E and gs during the vegetative phase when compared to the flowering stage.…”
Section: Resultsmentioning
confidence: 99%
“…Husen et al stated that the application of paclobutrazol 5 mL L -1 on a 5 yr old hybrid mango could accelerate during flowering, and increased the number of fruit yield [5]. Furthermore, Sarker et al stated that paclobutrazol could improve fruit yield, quality, and accelerate flowering in Amaprali varieties [2]. This result, was similar to the mangosten [11] and Tommy Atkins mango in Ethiopia [12].…”
Section: Effect Of Paclobutrazol + Organic Fertilizer On Flowering Anmentioning
confidence: 86%
“…Indonesian mango production was increase 2 203 793 t in 2017 to 2 624 791 t in 2018 and the rank is 6th in the world after India, China, Thailand, Pakistan and Mexico [1]. While, in 2011 mango production reached 2 129 608 t, while the exports were 1 485 t, and imports were 989 t. This gap in mango production and export volume indicated that Indonesia's mango is less competitive in the global market [2]. This condition is caused due to i) incompatibility of Indonesian mango quality specifications to world market demand, ii) there isn't available comprehensive seed testing system, which able to guarantee the product uniformity, iii) there isn't sustainable breeding program, iv) the farmers didn't apply technological innovation yet, and v) there isn't an institutional system which integrates mango agribusiness component.…”
Section: Introductionmentioning
confidence: 99%